How and Why Does God Change?: Exploring the Logic of the Divine Shift After the Golden Calf - Middleton, J. Richard (Hebrew studies, 2025)
After the idolatry of the golden calf, God tells Moses that the covenant is effectively canceled and that he intends to destroy the Israelites and start over with Moses. Not only does Moses refuse the offer, he convinces God not to destroy Israel, and even to accompany them on the journey to the Promised Land (which God initially had refused to do). Finally, Moses receives from God a personal theophany (a revelation of divine glory), accompanied by a new revelation of the meaning of the divine name (beyond that given in Exodus 3). This new revelation signifies a change in God's modus operandi with Israel from a conditional to an unconditional covenant, evident from a comparison of Exod 20:4-6 with Exod 34:6-7. This essay explores the nature and significance of the shift between Exodus 20 and 34, grounded in God's mercy or love, while noting analogous shifts in Deuteronomy, Jeremiah, and Ezekiel. Through an examination of the pattern underlying these shifts, the essay reflects on what the significance of this pattern might be for understanding the complicated characterization of the God of Israel.